Solar cloth using TiO2 nanostructures based dye sensitized solar cell technique - Noor Faridah, Amat; Mohd Azlishah, Othman; Badrul Hisham, Ahmad; Rajan, Jose (Asian Research Publishing Network (ARPN), 2015)
Titanium dioxide (TiO2) nanostructures have been synthesized via hydrothermal method by manipulating some parameters to determine which condition show better performance. In general, TiO2 Degussa, P25 dissolve in alkaline solution. The solution was mixed by stirring for 15-30 minutes and put into Teflon sealed into an autoclave stainless steel tank and put in an oven without shaking or stirring during heating. After that, the autoclave is cooled at room temperature, the obtained sample was stirred with dilute hydrochloric acid (HCl) aqueous solution for 24 hour and then the sample was washed by using deionized water for several times until the pH values decreased. TiO2 nanostructures act as network in solar cloth to perform the movement of electron in the device to generate electricity. Solar cloth is describe as non-woven fiber cloth in which a dye-anchored wide band gap semiconductor, which is the electron conductor forms a percolating network in polymeric medium. Because of principles in dye sensitized solar cell is same as solar cloth where dye sensitized solar cell consists of dye-anchored metal oxide in the presence of electrolyte and two conducting glass plates (such as fluorine-doped indium tin oxide (FTO)). Dye sensitized solar cell (DSSC) will be used TiO2 nanostructures to fabricate the device. Moreover, the electrical conductivity of TiO2 nanostructures in the present of polymeric medium will be measured.